Decadent verse : an anthology of late Victorian poetry, 1872-1900 - Blyth, Caroline (Anthem nineteenth century studies., 2009)
Contents : "Decadent Art 1872-1900; Introduction; Comparative Prose 1872-1900; Proem: The Way We Live Now; Verse selections from William Frederick Stevenson, Alfred Lord Tennyson, Edward Lear, Dante Gabriel Rossetti, Mary E. Coleridge, Thomas Hardy, Alice Meynell, etc."--Pub. website